AKTIVITAS SITOTOKSIK EKSTRAK KARANG LUNAK Xenia sp. DARI TELUK MANADO, PROVINSI SULAWESI UTARA - Juniarti S Datula’bi; Robert A Bara; Fitje Losung; Remy EP Mangindaan; Ping A Angmalisang; Rose OSE Mantiri (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Bioactive compounds from the sea which are generally in the form of secondary metabolites have the potential to be developed as medicinal ingredients. Marine life can be used as an object of research and development, considering the many benefits that can be taken from the secondary metabolite compounds contained in it, especially compounds that have bioactivity. Soft corals are marine biota that have bioactivity, extracts from sost coral contain bioactive compounds that have cytotoxic, anti-tumor, anti-viral, anti-inflammatory, anti-fungal, anti-leukemic, and enzyme activity inhibitory properties. Some of the research results show that marine soft corals have a variety of structures and biological activities including antioxidant substances. Soft corals were extracted by maceration method and then evaporated. The cytotoxic activity of soft coral extract was tested using the BLSA method and then analyzed the data to find the concentration of mortality (LC50). The purpose of this study was to test the cytotoxic activity of soft coral Xenia sp. The results of this study were testing the cytotoxic activity of the sample Xenia sp., amounting to 20.89 ppm, and having strong toxic properties. Key words: BLSA, Soft coral Xenia sp., LC50, Cytotoxic